Die identitätsstiftende Region Räumliche Identitäten als transformative Kraft in Regionen - Bentlin, Felix; Dörner, Christine; Lackus, Felix; Million, Angela (Schriftenreihe Städtebau und Kommunikation von Planung, 2022)
The identification of individuals with the region as a manageable and influenceable framework is gaining in importance in times of uncertainty, increasing dissolution of boundaries and global networking. We have experienced this directly in the last few months due to corona-related restrictions, which at times extremely reduced general mobility and at the same time made us aware of our dependence on technical infrastructures. For some people, this has inevitably brought the issue of their own place of residence more to the fore.